p53 Expression in Gliomas - Shanmugavadivu, Aruna C.; Deepika, T.; Hemamalini, R.; Madhusudhanan, G.; Indhu, K.; Babu, N.C. Ramesh (International Journal of Applied Sciences and Biotechnology, 2015)
The p53 expression on Gliomas are used for subtyping of tumours. The samples were extracted from the paraffin embedded tissue blocks. The Grade IV and Grade II were tested by IHC (ImmunoHistoChemistry) staining procedures. The primary antibody used was p53. It was found that there is a high expression of p53 in Grade IV (82%) was Score 3 and low expression p53 in Grade II (18%) in which the score was 1. This is in contrast to previous studies of subtyping of Gliomas where, classical types have low expression of p53 and proneural type have high expression of p53. This subtyping was based on score 0 - 3. Score 0 has no positive nuclei, Score 1 has 10% positive nuclei, Score 2 has 10 -30% positive nuclei while score 3 has >30% of positive nucleus. Int J Appl Sci Biotechnol, Vol 3(3): 479-482